Propellar shaped triple bond rigidified D-A-π-A triphenylamine dye as back electron interceptor in iodine and cobalt electrolyte DSSCs under full sun and indoor light. (1st March 2021) - Yoosuf, Muhammed; Pradhan, Sourava C.; Sruthi, M.M.; Soman, Suraj; Gopidas, Karical R.
Graphical abstract: Highlights: Custom designed novel D-A-π-A organic dye (TPAA8) for alternate cobalt electrolytes. TPAA8 achieved an efficiency of 6.40 ± 0.05% with 124% improvement in PCE with respect to TPAA1 (2.55 ± 0.13%) employing [Co(bpy)3 ] 2+/3+ electrolyte. TPAA8 proved to be an efficient candidate for indoor light harvesting delivering a PCE of 11.03 ± 1.7% using [Co(bpy)3 ] 2+/3+ electrolyte under 1000 lux LED illumination. Abstract: In the present manuscript, we report the synthesis and characterization of a new molecularly engineered triple bond rigidified D-A-π-A propeller shaped triphenylamine dye having benzothiadiazole as auxiliary acceptor (TPAA8). We compared the behavior of TPAA8 with the parent dye TPAA1 in D-π-A architecture without auxiliary acceptor, which was reported previously from our group (Vinayak et al., 2016). TPAA8 was found to be efficient in harvesting light and was having a favourable energetics suitable to realize forward electron transfer process in fabricated devices. TPAA8 with the introduction of auxiliary benzothiadiazole acceptor proved to be a promising candidate in preventing recombination with conventional iodine and alternate cobalt based redox electrolytes which was studied in detail employing various optical and electrical perturbation techniques. With alternate cobalt electrolyte ([Co(bpy)3 ] 2+/3+ ) TPAA8 delivered an improved performance of 6.40 ± 0.05%, which is an improvement of 124% in power conversion efficiency compared to the parent TPAA1 sensitizer devoid of auxiliary acceptor having an efficiency of 2.85%. TPAA8 also proved to be an efficient candidate for indoor light harvesting delivering a power conversion efficiency of 11.03 ± 1.7% employing [Co(bpy)3 ] 2+/3+ redox mediator under 1000 lux warm white LED illumination.